Assessment of Incidence of Familial Hypercholesterolemia in Young Patients With Premature Acute Myocardial Infarction - Ali, Sajid; Shuaib Abid, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Familial hypercholesterolemia (FH) is an autosomal dominant lipid disorder associated with significantly increased risk of premature atherosclerotic cardiovascular disease. Despite its high global prevalence and clinical relevance, FH often remains underdiagnosed, particularly in South Asian populations where cardiovascular events occur earlier. Objective: To determine the incidence of familial hypercholesterolemia in patients with acute myocardial infarction. Methodology: A prospective study was conducted in the Cardiology Department of Punjab Institute of Cardiology Hospital, Lahore from April 2024 to April 2025. A total of 100 patients who had experienced a type I premature acute myocardial infarction were included in the study.The incidence of familial hypercholesterolemia by Dutch Lipid Clinic Network score by using the personal and family history of premature cardiovascular diseases and level of low-density lipoprotein cholesterol.A DLCN score of less of 3 indicated no FH, 3-5 indicated possible FH, a score of 6-8 indicated probable FH and a score >8 indicated definite FH. Results: A total of 48 (48%) patients did not have FH, 45 (45%) had possible FH and 7 (7%) had definite or probable FH. The cardiovascular risk factors of premature myocardial infarction. Familial hypercholesterolemia was the strongest predictor (aOR: 39.2 (18.8-80.3), p<0.0001). Male gender (aOR: 2.9 (2.8-4.0), p<0.0001), smoking (aOR: 7.1 (6.3-9.2), p <0.0001) and diabetes (aOR: 3.0 (2.2-4.4), p<0.0001) were also significant determinants of premature MI. Conclusion: There is a low incidence of familial hypercholesterolemia in patients with premature myocardial infarction. Regular screening is required to timely diagnose FH in general population and reduce risks.